Development of an enzyme‐linked immunosorbent assay based on the monoclonal antibody of Bombyx mori to detect ancient silk. (15th February 2019) - Zheng, H. L.; Ma, C.; Dai, X. J.; Zhou, Y.
Abstract : Identifying the traces and residues of unearthed silk fibres is crucial for further analysis and study. In this study, an enzyme‐linked immunosorbent assay (ELISA) based on the monoclonal antibodies specific to Bombyx mori fibroin was developed in order to for detect ancient silk. Five monoclonal antibodies were successfully prepared based on fibroin hydrolysate, and four had a high specificity for mulberry silk. Furthermore, they could be used to discern B. mori fibre from tussah fibre and eri fibre. The ELISA standard curve of the most sensitive monoclonal antibody, anti‐Silk Fibroin (SF)‐3, was y = 0.022 x + 0.177 ( R 2 = 0.998), and the detection limit was 4.65 ng/ml. Using this antibody, we successfully identified five ancient mulberry silk samples from different time periods. The results suggest that ELISA assays based on monoclonal antibodies can be used as an immunological testing method for unearthed silk fibre.